BULI-BULI KERAMIK KOLEKSI MUSEUM BALI KAJIAN POLA HIAS DAN PERIODISASI - Kusumawati, Ni Ketut Ayu (Humanis; Volume 6. No. 3. Maret 2014, 2014)
Balinese society is known as an open society, a dynamic, a relationship that has continued since prehistoric times. Relations with the outside world brings culture, Balinese civilization became more complex, varied and unique. Archaeological evidence, and history has shown openness of the people of Bali, it appears that the Balinese had a long interaction with the outside world. Historical evidence that almost scattered throughout the corners of Bali and most of the collection of the Museum of Bali. However, the data that has not been adequately identified, thus not providing a thorough and comprehensive explanation. one of them is the possibility ceramics at that time became a valuable object in the kingdom, since at that time the only possibility of the nobility or high social status who has a collection of ceramics. One of the Bali Museum is a collection of ceramic jar. Ceramic jar for 83 pieces that have decorative patterns and a variety of glazes. Based decorative patterns, and glazes the pot, it will help reveal where it came from and periodization. Origin and periodization ceramic jar is as follows. Derived from the Chinese Ching Dynasty 18-19 century, China 20 Century, Vietnam 16-17 Century, Vietnam Century 18-19, Vietnam 15-16 century, Thailand Swankhalok 15-16 century, China 19-20 Century, China Ming Dynasty 16-17 Century, China Yuan-Ming Dynasty Century 14-15, Thailand Swankhalok 14-15 Century, Vietnam 14-15 Century, China Yuan Dynasty 13-14 Century, Vietnam Century -14, China 14-16 Century, and of Chinese 17-18 Century.
Keywords: Jarlet, Ornamental pattern, Glaze and Periodization